Effect of planting time and fertilizer dose on growth, yield and quality of parthenocarpic cucumber (Cucumis sativus) grown under polyhouse and nethouse conditions - MARAGAL, S Y; SINGH, A K; BEHERA, T K; MUNSHI, A D; DASH, SUKANTA (The Indian Journal of Agricultural Sciences, 2018)
An experiment was conducted to study the effect of planting time and fertilizer dose on growth, yield and quality of cucumber (Cucumber sativa L.) var. Pusa Seedless Cucumber 6 under two different protected structures. Experiment was laid out in factorial randomized block design with 3 replications. The treatments were formulated with four fertilizer levels (15:7:16, 20:12:21, 25:17:26 and 30:22:31 kg NPK/ha) and three date of plantings (15 August, 1 September and 15 September) under two different protected structures (insect proof nethouse and naturally ventilated polyhouse). Among the combinations, 15 September planting with 30:22:31 kg NPK/ha showed highest interaction effect for number of fruits/plant (20.20), fruit weight (134.11 g), yield/plant (2709.1 g), yield/1000 m2 (180.61 q), nitrogen (59 mg/100 g), phosphorus (27.33 mg/100 g), potassium (150.0 mg/100 g), calcium (11.29 mg/100 g), iron (0.23 mg/100 g) and zinc (0.22 mg/100 g) content of fruit under polyhouse. Based on these findings, it is recommended that the application of fertilizers at the rate of 30:22:31 kg NPK/ha on 15 September planting under naturally ventilated polyhouse is economical and found suitable for the successful growth, yield and quality of cucumber for higher productivity.